If it's not what You are looking for type in the equation solver your own equation and let us solve it.
z in (-oo:+oo)
(3/7)*z = -3/8 // + -3/8
(3/7)*z-(-3/8) = 0
(3/7)*z+3/8 = 0
3/7*z+3/8 = 0 // - 3/8
3/7*z = -3/8 // : 3/7
z = -3/8/3/7
z = -7/8
z = -7/8
| 6.2(x+-3)+-4.2=33 | | 9m+10-14m=15 | | 6*9-6/2 | | 16x(36/9 | | x/-18.3=-5 | | 24a+3(2a-5)=51 | | 8/16b-4/16b | | 5x9-6/2 | | -12x+-1y=21 | | 9-5x=2x-19 | | y=(0.0025s^2+0.05s+1)(s^2+31.5s+250)+0.39 | | h=66+173t+-16t^2 | | 2/3r=1/5 | | -8.3-(-3.7)+5.2= | | y-19.6=56 | | 5-x(4+7)=35 | | y^2+10y+x+27=0 | | 95000/6 | | 5-2y=37 | | 23+y=-19 | | h=-16t^2+173t+66 | | x^2+2y^2=576 | | (5x-3)(6x-9)= | | -15+3x=-6y | | 5+nover-3=14 | | 34=9-34 | | 2x=3x+13-9 | | Ln*(2x-3)+Ln*(x-4)=2*Ln*2 | | a/9-4=-11 | | -3=0+b | | 7d-4d+d+6=6d | | 5.3x=-12 |